Writing of nanowires via high viscosity-induced nano diffusive layer. Issue 45 (13th November 2017) - Mao, Sifeng; Zhang, Yong; Li, Haifang; Zeng, Hulie; Lin, Jin-Ming; Uchiyama, Katsumi
Abstract : A nano reduced diffusive layer was firstly presented for printing nanostructures of materials by using a millimeter-sized chemical pen. Abstract : Surface patterning and modification are common approaches to deriving different functions in distinct areas on the sample surface. The development of a flexible, region-selective, controllable method capable of localized patterning and modification in high spatial resolution requires a new principle to generate micro and nano-scale reagent areas. In this work, we report a high viscosity-induced nano diffusive layer for locally printing nano polymer wires onto a substrate. Using a millimeter-sized fluidic device, a reduced diffusive layer on the nanoscale was achieved by increasing the viscosities of injected solutions. The reduced diffusive layer, which functioned as an open reactor, is successfully explored in micro and nano-polymer wire fabrication. Multiple dominant parameters were explored, and consequently, a resolution as small as 800 nm was attained. The nano diffusive layer in the open environment was demonstrated to be a useful tool for localized chemistry. Furthermore, it has potential in nano-electrode assembly, nano-circuit manufacture, localized chemical modification and subcellular treatment.